2009
DOI: 10.1007/s00464-009-0416-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of routine intraoperative endoscopy in elective laparoscopic colorectal surgery: can it further avoid anastomotic failure?

Abstract: Background Anastomotic complications such as leakage and bleeding remain among the most serious complications of laparoscopic colorectal surgery. No perfect method exists for accurate and reliable avoidance of these catastrophes. This study aimed to study the usefulness of routine intraoperative endoscopy (RIOE) by comparing the surgical outcomes for RIOE patients with those for selective intraoperative endoscopy (SIOE) patients. Methods A retrospective chart review was performed for consecutive patients who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 22 publications
2
61
0
2
Order By: Relevance
“…The thirteen reviewed studies included a total of N=3,023 patients (Table 3), [16,17,[19][20][21][22][23][24][25][26][27][28][29]. Study sample size and design was variable.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The thirteen reviewed studies included a total of N=3,023 patients (Table 3), [16,17,[19][20][21][22][23][24][25][26][27][28][29]. Study sample size and design was variable.…”
Section: Resultsmentioning
confidence: 99%
“…Suture repair (74.7%) was the most common method of anastomosis correction used followed by takedown and re-anastomosis (17.3%) and diversion (8.0%). No significant differences in intraoperative leak rates were found were found across anastomosis types (staple: 4.9%, suture: 2.3%, and compression: 0.0%, p=0.066) in the 10 studies that reported leak based on type of anastomosis employed [16,[19][20][21][22][24][25][26][27][28]. Six articles reported on the rate of intraoperative leaks by surgical technique used (laparoscopic v. open) [22,[25][26][27][28][29].…”
Section: Search Term Description Definitionmentioning
confidence: 94%
See 2 more Smart Citations
“…Direct insufflation of air at the level of the anastomosis by intraoperative colonoscopy (IOCS) may be reliable for ensuring adequate intraluminal pressure to demonstrate a leak. The use of IOCS allows direct visualization and testing with the ALT for anastomotic defects [8,9].…”
Section: Introductionmentioning
confidence: 99%